2021
DOI: 10.2224/sbp.10241
|View full text |Cite
|
Sign up to set email alerts
|

Psychological empowerment and work burnout among rural teachers: Professional identity as a mediator

Abstract: We examined the relationship between psychological empowerment and work burnout as mediated by professional identity. Participants were 650 primary and secondary school teachers from nine rural provinces in China. The results indicate that both psychological empowerment and professional identity were significantly and negatively related to work burnout, and that psychological empowerment was significantly and positively associated with professional identity. Furthermore, professional identity partially mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 0 publications
3
19
0
Order By: Relevance
“…Professional identity entails a complex synthesis of thoughts, experiences, and behaviors associated with a particular profession and work role. 62 High levels of professional identity are associated with a clear understanding of the job, as well as flexibility to adapt and adjust role expectations. 63 Teachers who strongly identify with their profession are more likely than their peers to experience a sense of belonging and congruence between their perceptions of their self-identity and professional identity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Professional identity entails a complex synthesis of thoughts, experiences, and behaviors associated with a particular profession and work role. 62 High levels of professional identity are associated with a clear understanding of the job, as well as flexibility to adapt and adjust role expectations. 63 Teachers who strongly identify with their profession are more likely than their peers to experience a sense of belonging and congruence between their perceptions of their self-identity and professional identity.…”
Section: Discussionmentioning
confidence: 99%
“… 59 , 62 Low levels of professional identity are associated with feelings of insecurity regarding one’s professional value, which can lead to a state of indifference and consequent hopelessness and depression. 62 , 63 …”
Section: Discussionmentioning
confidence: 99%
“…The higher the score, the higher the degree of identification with the engaged profession. This scale was also proven to be highly reliable and valid in different studies, especially when the instruments were used with Chinese samples [ 16 , 19 ]. Cronbach’s coefficient was 0.93 for this scale in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Psychological empowerment refers to the synthesis of psychological states or cognition experienced by an individual [ 12 , 13 , 14 , 15 ]. Previous research found that both professional identity [ 12 , 16 , 17 ] and career satisfaction [ 18 , 19 , 20 ] are positively correlated with psychological empowerment. According to Cognitive Evaluation Model Theory (CEMT), individuals evaluate themselves and their career condition in conjunction with their own and others’ perspectives, and individuals with positive psychological empowerment would gain a stronger sense of meaning in their work [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Third, the effect of individual resources (here, psychological capital, professional identity and positive coping) was taken into account on the disposition of teacher burnout profiles and the latent transition of different profiles over time. These resource factors were confirmed to be important for teacher burnout [ 6 , 9 , 22 ]. Our study has the potential to produce a variety of information concerning the link between individual resources and burnout profiles and their roles in the transition of different burnout profiles, which is valuable for practical work.…”
Section: Introductionmentioning
confidence: 99%